Recombination and selection pressure in the ipomovirus sweet potato mild mottle virus (Potyviridae) in wild species and cultivated sweetpotato in the centre of evolution in East Africa - Tugume, Arthur K.; Mukasa, Settumba B.; Kalkkinen, Nisse; Valkonen, Jari P. T. (Journal of general virology, 2010)
Sweet potato mild mottle virus (SPMMV) is the type member of the genus Ipomovirus (family Potyviridae). SPMMV occurs in cultivated sweetpotatoes (Ipomoea batatas Lam.; Convolvulaceae) in East Africa, but its natural wild hosts are unknown. In this study, SPMMV was detected in 283 (9.8 %) of the 2864 wild plants (family Convolvulaceae) sampled from different agro-ecological zones of Uganda. The infected plants belonged to 21 species that were previously not known to be natural hosts of SPMMV. The size of the SPMMV coat protein (CP) was determined by Western blot analysis, N-terminal protein sequencing and peptide mass fingerprinting. Data implicated a proteolytic cleavage site, VYVEPH/A, at the NIb/CP junction, resulting in a CP of approximately 35 kDa. Nearly complete sequences of 13 SPMMV isolates were characterized. Phylogenetic analysis of non-recombinant CP-encoding sequences placed five isolates from wild species sampled in the central zone of Uganda into a separate cluster. Recombination events were detected in the 59- and 39-proximal parts of the genome, providing novel evidence of recombination in the genus Ipomovirus. Thirteen amino acids in the N terminus of the P1 protein were under positive selection, whereas purifying selection was implicated for the HC-Pro-, P3-, 6K1- and CP-encoding regions. These data, supported by previous studies on ipomoviruses, provide indications of an evolutionary process in which the P1 proteinase responds to the needs of adaptation.
Keywords: Selection pressure; Ipomovirus sweet potato mild mottle virus (Potyviridae); Wild species; Sweetpotato; East Africa